Duration of pairing and use of allosperm in Biomphalaria glabrata (Gastropoda: Planorbidae) Duração do acasalamento e uso do aloesperma em Biomphalaria glabrata (Gastropode: Planorbidae) - Marc Vianey-Liaud; Henri Nassi; Felix Lancastre; Jacques Dupouy (Memorias do Instituto Oswaldo Cruz, 1989)
Virgin homozygous black pigmented and albino Biomphalaria glabrata are paired during a period varying from 1 to 20 days. The rate of cross-fertilized parents is statistically similar for the various lengths of pairing. As a whole, nearly 80% of the albino snails produce a pigmented progeny. This production begins as soon as the snails are mated and continues after their separation. To measure the actual use of the allosperm, its use during the postmating period must be added to the length of mating. So, it appears that the real use of the allosperm is statistically constant (mean slightly inferior to 8 weeks) and not related to the length of the previous pairing. Espécimes virgens de Biomphalaria glabrata (um melâncio e um albino) são acasalados durante um período variável de 1 a 20 dias. A proporção de espécimes parentais albinos fecundados por cruzamento é semelhante estatisticamente para os diversos períodos de acasalamento. Em conjunto, cerca de 80% dos albinos produziram descendência pigmentada. Essa produção começa assim que os moluscos são acasalados e continua depois que são separados. Para medir a utilização real do aloesperma, sua utilização durante o período de pós-acasalamento. Parece, assim, que a utilização real do aloesperma é estatisticamente constante (média ligeiramente inferior a oito semanas) e não relacionada a duração do acasalamento anterior.